2003
DOI: 10.1063/1.1592004
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and field emission of conducting poly (3,4-ethylenedioxythiophene) nanowires

Abstract: Conducting poly (3,4-ethylenedioxythiophene) nanowires were synthesized by using an electrochemical polymerization method with a nanoporous template. Scanning and transmission electron microscopy confirmed the formation of conducting polymer nanowires (CPNWs) with an open end. The formation and the electrical properties of the CPNWs formed were dependent on synthetic conditions, such as the doping level, the polymerization time, and the applied current. The measured electrical conductivity of a single strand o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(25 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…http Conducting polymers combined with SWCNTs are quite promising for using as lightweight microwave absorbers. One of the most famous conducting polymers, poly (3,4-ethylenedioxythiophene) (PEDOT), is an appealing candidate to combine with SWCNT due to its high conductivity, low density and excellent electrochemical stability, which could be resistant to the corrosion as well as be favorable for the practical application in comparison to the metallic particles [11,[21][22][23][24]. Moreover, the easy processibility of PEDOT allows to be designed for various nanostructures of the composites via numerous strategies [25].…”
Section: Introductionmentioning
confidence: 99%
“…http Conducting polymers combined with SWCNTs are quite promising for using as lightweight microwave absorbers. One of the most famous conducting polymers, poly (3,4-ethylenedioxythiophene) (PEDOT), is an appealing candidate to combine with SWCNT due to its high conductivity, low density and excellent electrochemical stability, which could be resistant to the corrosion as well as be favorable for the practical application in comparison to the metallic particles [11,[21][22][23][24]. Moreover, the easy processibility of PEDOT allows to be designed for various nanostructures of the composites via numerous strategies [25].…”
Section: Introductionmentioning
confidence: 99%
“…in electronic and optoelectronic devices, photovoltaic solar cells, nanocomposite and hybrid solar cells, energy storage and conversion devices (batteries, fuel cells and supercapacitors, rechargeable batteries, fuel cells), electrocatalysis, sensors, membranes, biomaterials [246,247], such systems may represent a source of nanostructured conjugated polymers, e.g. nanowires for field-emission cells [248].…”
Section: Conducting Polymers Grown Inside Inert Matrixmentioning
confidence: 99%
“…The authors have observed threshold field of 5-6 V/μm corresponding to emission current density of 0.01 mA/cm 2 . Field emission studies on poly(3,4-ethylenedioxythiophene) (PEDOT) nanowires, doped and de-doped polypyrrole, PANI and PEDOT nanotubes and nanowires have been reported by Kim and his group [11,12]. Li et al have reported field emission characteristics of aniline and pyrrole copolymer nanofibers [13].…”
Section: Introductionmentioning
confidence: 96%
“…Since the 1-D nanostructures, owing to their high aspect ratio, offer unique advantages for their practical application as field emitters, attempts have been made to synthesize conducting polymers in 1-D nanometric form and study their field emission (FE) characteristics. Followed by the first report on FE properties of poly(3-octythiophene) by Musa et al, various research groups have carried out FE investigations of different conducting polymers and nanocomposites [9][10][11][12][13][14][15][16][17][18][19][20]. Wang et al have synthesized polyaniline (PANI) nanofibril array using AAO template and reported FE behaviour [10].…”
Section: Introductionmentioning
confidence: 96%